2011
DOI: 10.1002/etc.540
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants in blood plasma of satellite‐tracked adult male loggerhead sea turtles (Caretta caretta)

Abstract: Risks from persistent organic pollutants (POPs) remain largely a mystery for threatened loggerhead sea turtles (Caretta caretta). The present study examines regional-scale POP differences in blood plasma from adult male C. caretta based on movement patterns. Turtles were captured near Port Canaveral, Florida, USA, in April of 2006 and 2007 and fitted with satellite transmitters as part of a National Marine Fisheries Service-funded project. Residents (n = 9) remained near the capture site, whereas transients (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 30 publications
5
30
0
5
Order By: Relevance
“…Recent research revealed that adult loggerheads using northern foraging grounds in the MAB have higher concentrations of organic pollutants than turtles that use waters off central Florida, and our results support the hypothesis that this may be due to spatial structuring of foraging grounds by population (Ragland et al 2011). Similarly, a recent study found that loggerhead eggs laid in a northern nesting beach in North Carolina had higher organic concentration of pollutants than eggs laid in southern nesting beaches in Florida (Alava et al 2011).…”
Section: Conservation Implicationssupporting
confidence: 88%
“…Recent research revealed that adult loggerheads using northern foraging grounds in the MAB have higher concentrations of organic pollutants than turtles that use waters off central Florida, and our results support the hypothesis that this may be due to spatial structuring of foraging grounds by population (Ragland et al 2011). Similarly, a recent study found that loggerhead eggs laid in a northern nesting beach in North Carolina had higher organic concentration of pollutants than eggs laid in southern nesting beaches in Florida (Alava et al 2011).…”
Section: Conservation Implicationssupporting
confidence: 88%
“…4B), but does not necessarily support a latitudinal eVect on coastal waters from equator to polar regions because 15 N of primary producers slowly decreases at latitudes north of the Delaware estuary (McKinney et al 2010). The probable human inXuence revealed in the 15 N signatures of males in northern waters corresponds with the elevated concentrations of persistent organic pollutants recently found in the same male loggerheads (Ragland et al 2011).…”
Section: Variation In 13 C and 15 N Among Satellite-tracked Male Loggmentioning
confidence: 88%
“…Changes through time in the relative composition of individuals from a particular foraging ground observed in a breeding area may provide evidence of threats to which turtles are exposed (Hatase et al 2002;Zbinden et al 2011). For example, in the NWA, turtles using northern foraging grounds are at a higher risk of sublethal toxic eVects from high concentrations of organic pollutants than are southern foragers (Ragland et al 2011).…”
Section: Implications Of the Geographic Variation Of Isotopic Signaturesmentioning
confidence: 99%
“…No presente estudo, puderam-se observar correlações nas concentrações de OCs nos tecidos adiposo e hepático conforme descritas por Keller et al (2004a) (RAGLAND et al, 2011). No entanto, é provável que a tendência da diminuição das concentrações não se deva unicamente ao fenômeno de diluição, mas também ao tamanho amostral (KELLER et al, 2004b).…”
Section: Relação Entre Porcentagem De Lipídeos Eunclassified
“…Os resultados obtidos com amostras sanguíneas refletem uma exposição recente a toxinas (LABRADA-MARTAGÓN et al, 2011). Por esse motivo, alguns estudos como, por exemplo, os realizados em matrizes como sangue ou ovos (SWARTHOUT et al, 2010;KOMOROSKE et al, 2011;LABRADA-MARTAGÓN et al, 2011;RAGLAND et al, 2011;IKONOMOPOULOU;WHITTIER, 2012) (KELLER et al, 2004b). Desta maneira, os resultados obtidos no presente estudo devem ser interpretados com cuidado, pois algumas amostras vieram de animais encalhados, às vezes em condições corporais pobres e desconhecendo-se a data exata e causa do óbito.…”
unclassified